Problema de Programação Linear - PPL: uma abordagem pelo método simplex - Ganske, Dayana Cristina (2024)
Linear programming aims to maximize or minimize a linear function subject to a set of linear constraints that define a convex polyhedron. The primary objective of this work is to implement the Simplex algorithm, a tool used for solving linear programming problems. This study proposes to present a chronological examination of key concepts necessary for the construction of the Simplex method, beginning with a review of linear algebra, real analysis, analysis in Rn and cone characterization. Regarding the optimization problem, general concepts about the subject are studied, followed by the concepts of linear programming. Also that, a brief study on polyhedra is presented, which defines a feasible region addressed in the problems of this text. The final phase of the work is dedicated to the study and development of the Simplex Method, accompanied by solved problems.